UTIW: Urinary Tract Infection Workflow System towards early and automatic detection of Urinary Infection during pregnancy - Hirales-Carbajal, Adán; Escobedo Bravo, Lizbeth Olivia (My University, 2019)
Worldwide Fetal-Maternal morbidity and mortality is frightfully high. Most of these diseases occur in developing countries. One of the main reasons of this problem, after gestational hypertension and complications in childbirth, is infections. Infections are most of the times hard to detect by the patient. Urinary Tract Infections (UTI) during pregnancy is one of the main reasons of fetal-maternal morbidity and mortality in Mexico. Among others, the pervasiveness and heterogeneity of data generated complicates early diagnosis and treatment of UTI. In this study, two hundred, randomly chosen, medical records and notes corresponding to pregnant patients with and without UTI were analyzed to find association rules for UTI positive cases. We found that most of the occurring rules show how physicians strive toward discovering the presence of sexually transmitted diseases or infections and that patients are less likely to be auscultated for symptoms that lead to miscarriage. A four-phase data analysis workflow, referred to as UTIW (Urinary Tract Infection Workflow) for discovering association rules in patients with UTI is proposed.
Keywords: Applied computing; Life and medical sciences; Health care information systems; Campus Tijuana